Post-foundational Ontology and the Charge of Social Weightlessness in Radical Democratic Theory: A Response to Lois McNay’s The Misguided Search for the Political - Tom N. Henderson (Janeway JS, 2017)
This article responds to the accusation made by Lois McNay in The Misguided Search for the Political that much radical democratic theory is ‘socially weightless’ as a direct result of its turn towards an ontological understanding of the political. It argues that the social weightlessness identified in the work of the particular theorists McNay singles out for critique is not the result of the ontological approach per se. After briefly summarising McNay’s argument, Oliver Marchart’s ontology of political difference is used to defend the ‘search for the political’ against four aspects of McNay’s argument: the status of the ontological in post-foundational thought, the question of universality in relation to the political, the relationship between the social and the political, and that between indeterminacy and agency. Following this, the methodology of the disclosing critique of social suffering that McNay puts forward as an alternative to the ontological paradigm will be examined. This will be shown not only to be compatible with such a paradigm, but to be rooted in the very same parts of Heidegger’s philosophy. Moreover, her approach is found to enhance the ontological approach to the political by recovering its hermeneutical dimension, and in turn reconnecting hermeneutics to the question of the body. These are steps which, if further built upon, could add not only social, but also fleshly weight to ontological theories of the political, strengthening the critical potential of radical democracy.